The Effect of Financial Knowledge, Financial Experience, and Locus of Control on Financial Management Behavior at Batik Msmes in Tuban - I Bagus Rendy Brahmastra; Ira Wikartika (International Journal Labs, 2023)
The global financial recession that occurs in Indonesia is now one of the phenomena that can reduce the stamina of the national economy. With the recession in 2023, it will have a negative impact on MSMEs in Indonesia. MSMEs have a positive influence on the Indonesian economy and regional economy, one of which is Tuban Regency which is a batik producing area, but its existence is still not widely known to people. In opening a business such as batik MSMEs, knowledge, experience, and locus of control are needed, in managing the finances of these batik MSMEs. This study is intended to identify how the influence of financial knowledge, financial experience and locus of control on financial management behavior in Batik MSMEs in Tuban. This research method is quantitative by taking a sample of 95 respondents and the distribution of this questionnaire is assisted by Google Form. The samples in this study were taken using probability sampling techniques. The sample consisted of respondents from the Batik MSME Center in Tuban. The data used in this study are primary data and secondary data. The analytical techniques used in this study are (PLS) with validity tests, reliability tests and hypothesis tests. The results of this study found that the variables of financial knowledge, financial experience, and locus of control had an effect and were significant on the variables of financial management behavior. Financial knowledge plays an important role in the financial management behavior of Batik MSMEs. The higher an individual's understanding of financial knowledge, the higher the level of financial management behavior, so that financial knowledge has a positive influence on financial management behavior in Batik MSMEs in Tuban.